Barriers to the utilisation of data gathered through information systems in the management of social welfare organisations - Salovaara, Samuel; Leinonen, Jaana; Silén, Marianne (Finnish Journal of eHealth and eWelfare, 2021)
Using the data collected through information systems in knowledge management is considered to be important when trying to increase the productivity and effectiveness of the social welfare field. However, barriers to data utilisation have been perceived, even when data are available. The utilisation of data has recently been supported nationwide through strategy work, projects, the development of legislation and the reform of the overall national information architecture. The article defines knowledge management as managing the knowledge refined from data. The study examined the barriers to information utilisation in knowledge management identified in public, private and third-sector organisations in the social welfare field. The article is part of a nationwide project to monitor and evaluate social and health care information system services. The data (n = 356) were collected during the spring and autumn of 2020 with an electronic form addressed to the persons in charge of the social services in organisations. In most organisations, one to four barriers to data utilisation were identified. Public organisations tended to experience more barriers compared with private and third-sector organisations, and large organisations experience more barriers than small ones. The most typical barriers were deficiencies in skills, resources and information systems. Based on the research results, it would be justified to direct support for data utilisation in the social sector to the organisational level—in addition to national and regional support—to realise the desired benefits of knowledge management.